2018
DOI: 10.3892/ol.2018.7880
|View full text |Cite
|
Sign up to set email alerts
|

Casticin inhibits the epithelial-mesenchymal transition in ovarian carcinoma via the hedgehog signaling pathway

Abstract: Abstract. Casticin inhibits migration, invasion and induced apoptosis in numerous cancer cells; however, the Hedgehog (Hh) signaling pathway is a key factor in the epithelial-mesenchymal transition (EMT). The present study aimed to assess whether casticin affects the expression of members of the Hh signaling pathway and EMT effectors in ovarian carcinoma. The ovarian cancer SKOV3 cell line was incubated in the presence of various concentrations of casticin or cyclopamine. Next, the expression levels of the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…When EMT occurs, the expression of E‐cadherin reduced while N‐cadherin expression increased. Reports had demonstrated that casticin‐inhibited EMT in ovarian carcinoma and hepatocellular carcinoma . In the present study, we demonstrated that casticin induced the expression of E‐cadherin but inhibited the expression of N‐cadherin through Western blotting, which indicates that the inhibition of cell invasion and migration by casticin may be companies with the suppression of EMT.…”
Section: Discussionsupporting
confidence: 64%
“…When EMT occurs, the expression of E‐cadherin reduced while N‐cadherin expression increased. Reports had demonstrated that casticin‐inhibited EMT in ovarian carcinoma and hepatocellular carcinoma . In the present study, we demonstrated that casticin induced the expression of E‐cadherin but inhibited the expression of N‐cadherin through Western blotting, which indicates that the inhibition of cell invasion and migration by casticin may be companies with the suppression of EMT.…”
Section: Discussionsupporting
confidence: 64%
“…Among the new EMT marker genes, GLI1 and SMO are two genes belong to the Hedgehog pathway. Increasing evidence suggests that Hedgehog‐GLI1 signaling plays an important role in EMT of several tumor types, including ovarian cancer, gastric cancer, and pancreatic cancer, where GLI1 expression is essential for cancer cell survival and facilitates the migration and invasion of cancer cells by promoting the EMT process . Although these two biomarkers need to be confirmed in larger cohorts, our results show that both GLI1 and SMO tend to be upregulated in metastatic tumors in comparison with primary tumors, and cooverexpression of GIL1/SMO is associated with HNSCC metastasis, indicating the importance of the Hedgehog pathway to contribute to hypoxia‐induced EMT and metastasis, and the prognostic significance of GLI1/SMO in HNSCC patients.…”
Section: Discussionmentioning
confidence: 56%
“…Among the new EMT marker genes, GLI1 and SMO are two genes belong to the Hedgehog pathway. Increasing evidence suggests that Hedgehog-GLI1 signaling plays an important role in EMT of several tumor types, including ovarian cancer,43 gastric cancer,44 and pancreatic cancer,…”
mentioning
confidence: 99%
“…Glioma-associated oncogene-1 (Gli-1) and EMT-associated hedgehog factors, including Twist1 levels, were also reduced. The hedgehog signaling pathway transforms key information necessary for cell differentiation [102]. In this way, casticin can inhibit cell invasion, migration and viability in human ovarian cancer cell lines.…”
Section: Casticin and Ovarian Cancermentioning
confidence: 99%